Bioinformatics analysis of miRNAs germacrone protection on diabetic nephropathy - Binqi Wang; Wenfang He; Zhixuan Xie; Jinshi Zhang; Yan Ren; Qiang He; Juan Jin (Scientific Reports)
Abstract Diabetes nephropathy (DN) is a prevalent and severe microvascular diabetic complication. Despite the recent developments in germacrone-based therapies for DN, the underlying mechanisms of germacrone in DN remain poorly understood. This study used comprehensive bioinformatics analysis to identify critical microRNAs (miRNAs) and the potential underlying pathways related to germacrone activities. Additionally, we established a DN mice model, which was treated with germacrone, to investigate how it altered the miRNA transcriptome in mice kidneys. RNA sequencing was also performed on the DN mice model with and without germacrone pre-treatment. Based on our results, we found 23 miRNAs were differentially expressed in the DN group compared to the controls, and a total of 14 miRNAs were differentially expressed between the DN group and the germacrone-treated group. In addition, we identified three miRNAs (mmu-miR-542-5p, mmu-miR-149-5p and mmu-miR-196a-2-3p) that were upregulated with the DN group and downregulated in the germacrone-treated group. Bioinformatics analysis suggested that autophagy and apoptosis were related to the pathogenesis of DN and germacrone treatment. Subsequently, the expression level of mmu-miR-542-5p, mmu-miR-149-5p and mmu-miR-196a-2-3p were validated in a validation dataset. Altogether, these findings add important knowledge on the pathogenesis of DN and the impacts of germacrone.